Synthesis and self-assembly of 1-deoxyglucose derivatives as low molecular weight organogelators - Wang, Guijun; Yang, Hao; Cheuk, Sherwin; Coleman, Sherman (Beilstein Journal of Organic Chemistry, 2011)
Low molecular weight gelators are an important class of molecules. The supramolecular gels formed by carbohydrate derived low molecular weight gelators are interesting soft materials that show great potential for many applications. Previously, we have synthesized a series of methyl 4,6-O-benzylidene-α-D-glucopyranoside derivatives and found that several of them are good gelators for water, aqueous mixtures of DMSO, or aqueous mixtures of ethanol. The gelation efficiency of these glycolipid derivatives is dependent upon the structures of their acyl chains. In order to understand the influence of the anomeric position of the sugar headgroup towards self-assembly, we synthesized a series of 1-deoxyglucose analogs, and examined their gelation properties in several solvents. Several long chain esters, including diacetylene containing esters, and aryl esters exhibited gelation in ethanol, aqueous ethanol, or aqueous DMSO. The synthesis and characterization of these novel analogs are reported.
Keywords: 1,5-anhydroglucitol; carbohydrate; hydrogelator; organogelator; self-assembly